Molecular Docking Of Cyclosenegalin A As Anticancer - Paat, Vlagia Indira; Aloanis, Anderson Arnold; Najoan, Jessika Maya Jovanka (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Cancer is recognized as a leading cause of death globally, responsible for approximately 14.5% of all deaths,. Cyclosenegalin A showed activity against DU-145 human prostate cancer cell line with IC50 of54.92.35μM. This study aims to investigate whether the cyclosenegalin A compound can interact with the target receptors 4IEH and potentially act as an anticancer candidate. The results of the study show that the docking of cyclosenegalin A with the 4IEH receptor yielded the best results, with an affinity value of -8.88 kcal/mol. The hydrogen bonding at the GLY 104, ASP 70, VAL 92, and GLU 95 amino acids was identical to that observed in the standard ligand, n-heteroarilsulfonamides. The interaction between cyclosenegalin A and the target receptor is effective, indicating that cyclosenegalin A holds potential as an anti-cancer candidate.